REMEDIASI MISKONSEPSI MELALUI MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, SHARE (SSCS) PADA MATERI SUHU DAN KALORI DI SMA NEGERI 1 SEPAUK - Meisa Erlinda Elen; Stepanus Sahala; Muhammad Musa (Jurnal Riset Multidisiplin Edukasi, 2026)
This research aims to look at the misconceptions experienced by students before and after implementing remediation and also to reduce misconceptions among students using the Search, Solve, Create and Share learning model. This research was carried out by collecting quantitative data with two instruments, namely a pre-test to find out students' misconceptions before remediation, and a post-test to find out misconceptions after remediation. After conducting the research, it was found that there was a decrease in the average percentage of students' misconceptions by 88.8%, whereas initially there were 88.5% misconceptions. After remediation was carried out using the SSCS learning model, the level of students' misconceptions decreased by 9.6%. . The SSCS learning model is effective in reducing the number of students who have misconceptions. This is also shown by the DQM value of 81% which is included in the high category.